Negative Stress Examination Under Anesthesia Reliably Predicts Pelvic Ring Union Without Displacement. Issue 4 (April 2017) - Whiting, Paul S.; Auston, Darryl; Avilucea, Frank R.; Ross, Daniel; Archdeacon, Michael; Sciadini, Marcus; Collinge, Cory A.; Sagi, Henry C.; Mir, Hassan R.
Abstract : Objectives: To identify the negative predictive value of examination under anesthesia (EUA) for determining pelvic ring stability and union without further displacement. Design: Retrospective cohort study. Setting: Two academic Level 1 trauma centers. Patients/Participants: Thirty-four adult patients with closed pelvic ring injuries treated over a 5-year period. Interventions: Pelvic stress EUA. Main Outcome Measures: Pelvic ring union and pelvic ring displacement at final follow-up. Results: Thirty-four patients with closed pelvic ring injuries who underwent pelvic EUA during the study period and had a negative examination (indicating a stable pelvis) were identified. Mean age was 38 years (range 16–76), and 19 patients (55.9%) were male. Twenty-two patients (64.7%) had Young–Burgess lateral compression (LC)-1 injuries with complete sacral fractures, 4 patients (11.8%) had LC-2 injuries, and 8 patients (23.5%) had anteroposterior compression (APC)-1 injuries. Eight patients (23.5%) had associated injuries requiring restricted weight-bearing on one or both lower extremities and were excluded from the analysis. Immediate weight-bearing as tolerated was permitted bilaterally in the remaining 26 patients. Mean pelvic ring displacement at the time of injury was 3.8 mm (range 1–15 mm) for LC injuries and 9.1 mm (range 2–20 mm) for APC injuries. Patients were followed for a mean of 8 months (range 3–34 months). At final follow-up, mean displacement was 3.7 mm (range 0–17 mm) for LC injuries and 7.1 mm (range 2–19 mm) for APC injuries. Mean change in displacement from injury to union was −0.1 mm for LC injuries and −2.0 mm for APC injuries, indicating decreased pelvic ring displacement at union. All patients were able to tolerate full weight-bearing bilaterally with no pain, and there were no instances of delayed operative fixation after negative EUA. Conclusions: Negative pelvic EUA after closed pelvic ring injury accurately predicts pelvic stability and union without displacement after nonoperative treatment with full weight-bearing bilaterally. Unless otherwise dictated by associated injuries, immediate weight-bearing as tolerated seems safe in patients with pelvic ring injuries who have had a negative EUA. Level of Evidence: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.